2008
DOI: 10.1515/ijamh.2008.20.3.275
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sex education on HIV knowledge and condom use among adolescent females in the Dominican Republic

Abstract: The Dominican Republic has witnessed a significant increase of HIV/AIDS in recent years, particularly among young women. Prior research suggested that sex education could be an effective tool in combating risky sexual behaviors in adolescents; yet, most of this research has been conducted with Caucasian study populations, resulting in limited generalizability to Latino populations. The present study sought to address this gap by examining the effects of sex education on HIV/AIDS knowledge and condom use among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…However, HIV prevention services that aim to reduce the risk of acquiring and transmitting infections among MSM and link infected MSM to treatment must be expanded to reduce HIV infections that are primarily spread through UAI [28]. Sex education programs are effective at increasing HIV/AIDS knowledge and condom use [29]. Future research on the causal mechanisms underlying the association between education and HIV/AIDS prevention should focus on how more advanced schooling enhances the cognitive skills needed for health reasoning [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, HIV prevention services that aim to reduce the risk of acquiring and transmitting infections among MSM and link infected MSM to treatment must be expanded to reduce HIV infections that are primarily spread through UAI [28]. Sex education programs are effective at increasing HIV/AIDS knowledge and condom use [29]. Future research on the causal mechanisms underlying the association between education and HIV/AIDS prevention should focus on how more advanced schooling enhances the cognitive skills needed for health reasoning [30].…”
Section: Discussionmentioning
confidence: 99%
“…Health Behaviors of Women Attitudes about gendered inequality mediate the relationship between women's education and safer-sexrelated behaviors. In the current study, sex education programs were confirmed to be effective in increasing HIV/AIDS knowledge and condom use, reducing the risk of unprotected intercourse and STIs, unplanned pregnancy and abortion, appropriate behavior, and mental health, and finally, preventing the sexual problems, family health, and appropriate gender identity (28,30,32). Moreover, the results of several studies represented that community empowerment-based HIV prevention was associated with significant improvements across HIV outcomes and setting (33,37,38).…”
Section: Discussionmentioning
confidence: 61%
“…Due to a significant increase in the rate of HIV/AIDS in Dominican Republic a Encuesta Nacional de Jovenes, (ENJOVEN), a collaborative survey (between the Instituto de Estudios de Poblaciöny Desarrollo, Asociaciön Dominicana Pro Bienestar de la Familia, Reproductive Health, Centers for Disease Control and Prevention) was performed on this country and the results indicated that sex education programs were effective in increasing HIV/ AIDS knowledge and condom use in young people (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prefer not to answer 21.4 (3) increase HIV knowledge and condom use [34]. In other populations, greater education is associated with lower prevalence of HIV [6], more accurate perception of HIV risk, and less stigma [4].…”
Section: Discussionmentioning
confidence: 99%